2003
DOI: 10.3136/fstr.9.372
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies on Fracture Characteristics of Food Gels Subjected to Uniaxial Compression and Torsion

Abstract: Stress developments in cylindrically shaped food gels were comparatively investigated by applying uniaxial compression and torsional deformation up to fracture. While torsion tended to result in earlier fracture with lower fracture stress and strain values, the true shear stress vs. true shear strain curves determined based on uniaxial compression and torsion tests were in good agreement up to the point of fracture in torsion in most cases examined. A typical fracture plane was observed at an angle approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Both gels can therefore be assumed to deform in a non-linear elastic manner and are rate independent. This finding agrees with the previous work on starch gels [7,13]. In addition, these figures reveal that fracture stress and fracture strain increase with increasing deformation rate, suggesting that the fracture behaviour of starch gels is rate dependent.…”
Section: Uniaxial Compression Testssupporting
confidence: 83%
“…Both gels can therefore be assumed to deform in a non-linear elastic manner and are rate independent. This finding agrees with the previous work on starch gels [7,13]. In addition, these figures reveal that fracture stress and fracture strain increase with increasing deformation rate, suggesting that the fracture behaviour of starch gels is rate dependent.…”
Section: Uniaxial Compression Testssupporting
confidence: 83%
“…The differences in the obtained fracture strain between gelatin and agar gels is primarily due to the polymer type and resulting gel microstructure. Ikeda, Sangu and Nishinari (2003) have shown that agar gels show lower fracture strain values when compared to gelatin. Also the study further reports that with increase in polymer concentration gelatin based gels have shown increments in fracture strain while a slight decrease was seen for agar based gels.…”
Section: Resultsmentioning
confidence: 99%
“…Ikeda et al . () compared the torsion and compression of cylindrical food gels. Since some elastic gels such as konjac and curdlan could not be fractured in conventional compression test, and such a gel may not be suitable for people with difficulty in mastication, torsion test is useful to determine rheological properties of such gels.…”
Section: Future Workmentioning
confidence: 99%
“…To understand the mastication in the mouth, however, these treatments should be extended to large deformation and fracture (Kawai et al 2008;Forte et al 2015;Gamonpilas et al 2009;Czerner et al 2016), and in addition, not only the deformation but also the flow should be incorporated, which seems to be a very complicated analysis. Ikeda et al (2003) compared the torsion and compression of cylindrical food gels. Since some elastic gels such as konjac and curdlan could not be fractured in conventional compression test, and such a gel may not be suitable for people with difficulty in mastication, torsion test is useful to determine rheological properties of such gels.…”
Section: Future Workmentioning
confidence: 99%